Filosofsʹka hermenevtyka jak naukovyj pidchid do doslidžennja biblijnych tekstiv = Philosophical Hermeneutics as Scientific Approach to the Investigation of Biblical Texts - Husak, Petro (Bogoslovskie razmyšlenija, 2018)
Contents, present in biblical texts, are data, accessible to rational knowledge, and hence — object of philosophical hermeneutics of texts as such. Taking into account the supra-temporal way of existing of texts, a researcher is akin to know, "how it is indeed", coming out of the direct meaning of text, and basing on the philological fact, that words have their primary meaning, which correctly reflects things and states of affairs in reality. A rational reflection makes to its research’ object the tradition of "exactly such interpretation of texts" and spellings of authorities, goes beyond their frames and checks them on their unimpeachability. Such checking is a "reasonable service" (cf.: Rom 12, 1): usage of the reflexive ability of reason, which belongs to human personhood as image of God.